A review of Hummā Danj (dengue fever) in Unani and conventional medicine - Imlaque, Mohd; Husain, Safder; Shewrwani, Arish Mohammad Khan; Bibi, Chand (International Journal of Research in Medical Sciences, 2025)
The global burden of Hummā Danj dengue fever (DF) and its severe manifestations, such as dengue haemorrhagic fever (DHF) and dengue shock syndrome (DSS), has escalated significantly in recent decades. Dengue viruses, transmitted primarily by Aedes mosquitoes, pose a substantial public health challenge, with an estimated 50-100 million infections annually and significant mortality. While traditionally viewed as a childhood illness, there’s emerging evidence of a shift towards older age groups experiencing more severe forms of the disease. Additionally, race, gender, rural settings and climate variability influence disease dynamics. Socioeconomic factors play a crucial role, with poorer countries facing greater challenges in disease prevention and control. The economic impact of dengue, akin to malaria, underscores the need for effective public health interventions. Improving case management, early detection and accurate monitoring are essential strategies. Diagnosis remains challenging due to variable test sensitivities and specificities. In Unani medicine, dengue fever is conceptualized within the framework of humoral pathology, with management focusing on symptomatic relief and supportive care. Overall, addressing the multifaceted challenges of dengue requires a comprehensive approach integrating medical, social and economic strategies.